Écrire la fragilité de l’existence humaine ou comment exprimer l’agonie (Bataille navale de Reinhard Goering, Pique-nique en campagne et Guernica de Fernando Arrabal) - Kaczmarek, Tomasz (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
In this article, the author studies the dramas which, while exposing the absurdityof war, express an apocalyptic vision of humanity doomed to its destruction. Whether it isReinhard Goering’s Sea battle or Arrabal’s dramas (Picnic on the Battlefield and Guernica) weare witnessing an obvious renewal of the tragedy. However, the authors do not apply therules specific to the canonical genre, but by shining a light on the precarious condition ofmodern man, they paint a world in its self-destruction where there is no place for catharsis.Tragic in its modernized version inevitably provokes the shaking of the dramatic formwhich testifies not only to human agony but also to that of dramatic art. In fact, the twoplaywrights undermine the main foundations of “absolute drama”, deconstructing the actionin the classic sense of the word and depriving their characters of their active attributesof a hero of traditional theater.